German law covering the public participation in planning and building infrastructure projects - Bothe, Anja (2018)
The analysis presented here focuses on the latest German legislation changes introduced in order to make the planning and building of infrastructure projects more harmonious and more effective. From a due-process perspective, International and European Environmental law played a pioneer role. by leading the German legislators to introduce an earlier public participation in its extremely complex system of spatial and sectorial planning. At first it mainly addressed sustainability. Then, after a few major infrastructure projects were confronted with massive resistance by the population affected, a rethinking about the citizens´ involvement at an early stage became necessary, aiming at streamlining and speeding up legally binding decisions on the more controversial infrastructure projects. As a result, the Administrative Procedure Code was expanded to incorporate the "Law for broadening the public participation and for the standardization of the procedures for determining sectorial plans". In order to debate, in an interdisciplinary way, the role that the law is able to play in communication procedures, this article discusses the essential factors impacting the different types of plans and planning. It then questions the strategies leading to acceptance of certain projects and the trade-offs between speed of implementation and the respect for public participation rights.